Primary intracranial malignant ectomesenchymoma in an adult: Report of a rare case and review of the literature. Issue 3 (25th March 2019) - Mahajan, Swati; Suri, Vaishali; Sharma, Mehar C.; Kedia, Shweta; Sardana, Hardik; Nakra, Tripti
Abstract : Malignant ectomesenchymoma (MEM) is an exceedingly rare rapidly progressing tumor of soft tissues of the central nervous system, believed to be derived from neural crest cells. The majority of cases have been observed in young children or adolescents. So far only 11 patients with intracranial manifestations (with confirmed clinicopathological data) have been documented. We report the first case of adult intracranial MEM in a 54‐year‐old man who presented with a 4 months history of headache and weakness of right side of the body. Magnetic resonance imaging showed a homogenously enhanced dural‐based lesion in the left fronto‐temporo‐parietal lobe with significant perilesional edema and mass effect. No metastatic disease was identified and the lesion was grossly resected. Histopathological and immunohistochemical examination revealed mature and immature neurons and bizarre astrocytes admixed with a mesenchymal spindle cell (rhabdomyoblastic) component. Specific risk factors that contribute toward the development of MEM are unknown. Due to the scarcity of reported cases the role of adjuvant therapy is unclear.